Epidemiology of Mycobacterium bovis Disease in Humans, the Netherlands, 1993–2007 - Majoor, Christof J.; Magis-Escurra, Cecile; van Ingen, Jakko; Boeree, Martin J.; van Soolingen, Dick (Emerging infectious diseases, 2011)
In the Netherlands, 1.4% of tuberculosis (TB) cases are caused by Mycobacterium bovis. After we admitted 3 patients with M. bovis infections to our reference hospital, we conducted a retrospective analysis of all M. bovis disease in the Netherlands during 1993-2007. We analyzed data from 231 patients for clinical, demographic, treatment, and outcome characteristics and for risk factors. Most patients were native Dutch (n = 138; 59.7%) or Moroccan (n = 54; 23.4%). Disease was mainly extrapulmonary (n = 136; 58.9%). Although 95 patients had pulmonary disease, person-to-person transmission did not occur, as shown by structural DNA fingerprinting analysis. Lymph node TB was more likely to develop in women (p<0.0001), whereas pulmonary M. bovis disease developed more frequently in men (p<0.0001). Diagnosis was accurate but delayed and led to inadequate treatment in 26% of the cases. Proportion of deaths from M. bovis disease was higher than that for M. tuberculosis disease.